Targeting the unfolded protein response in heart diseases. (1st July 2014) - Liu, Man; Dudley, Samuel C
Abstract : In neurological disease and diabetes, the unfolded protein response (UPR) has been investigated for years, while its function in heart disease is less well understood. All three branches of the UPR are involved in ischaemia/reperfusion and can either protect or impair heart function. Recently, UPR has been found to play a role in arrhythmogenesis during human heart failure, and blocking UPR has an antiarrhythmic effect. This review will discuss the rationale for and challenges to targeting UPR in heart disease.